A systematic review of measures of healthcare workers' vaccine confidence - Kofoworola O. Akinsola; Ayobami A. Bakare; Elisa Gobbo; Carina King; Claudia Hanson; Adegoke Falade; Sibylle Herzig van Wees (Taylor & Francis Group, 2024)
ABSTRACTHealthcare workers (HCW) perceptions toward vaccines influence patient and community vaccine decision making. In an era of rising vaccine hesitancy, understanding HCW vaccine confidence is critical. This systematic review aims to review instruments that have been validated to measure HCW vaccine confidence. We conducted a search in five databases in June 2023. Data was descriptively synthesized. Twelve articles describing 10 different tools were included. Most tools included dimensions or items on vaccine knowledge (n = 9), safety (n = 8), vaccine usefulness (n = 8), recommendation behavior (n = 8), and self-vaccination practice (n = 7). All, except one study, were conducted in high-income countries. There was variability in the quality of the validation process. There is limited existing literature on development and validation of tools for HCW vaccine confidence. Based on the tools currently available, the Pro-VC-Be tool is the most well validated. Further research needs to include low- and middle-income contexts.